「フジ」 コウロ (1980/81) ニ オケル ミナミ タイヨウ ヒョウメン カイスイ チュウ ノ クロロフィル α ブンプ - 渡辺, 研太郎; ワタナベ, ケンタロウ; 中嶋, 泰; ナカジマ, ヤスシ; Watanabe, Kentaro; Nakajima, Yasushi (1983)
P(論文) 第22次南極地域観測隊の海洋生物定常観測の一環として, 1980年12月から1981年3月にかけ, 「ふじ」航路に沿った南大洋インド洋区において表面海水中のクロロフィルα量を測定した。クロロフィルα濃度は亜熱帯水域で0.2mg/m^3以下と低く, 亜南極海域でやや高くなり, 南極収束線(AC)の北側では0.50,0.24mg/m^3の極大値が得られた。ACの南側の外洋域では概してクロロフィルα濃度は低かったが, ACのはるか南の58°S付近では0.84(南下航路上), 62°S付近では0.58mg/m^3(北上航路上)の高い値が測定された。1980年12月の西行航路上で行った測定において, 浮氷域の中ないしは近くでクロロフィルα濃度は極大を示し, 水温・塩分ともに低下した。定着氷に囲まれた氷湖中では0.66,0.80mg/m^3の高い濃度を測定した。これに対して北上航路上の浮氷域での値は低く, 西行航路上での結果と異なった。これらの結果より, 海氷とクロロフィルα濃度とが何らかの関係を持つことが示唆される。 The measurement of the chlorophyll α concentration of the surface water in the Southern Ocean was performed along the course of the icebreaker FUJI from December 1980 to March 1981 as a part of the 22nd Japanese Antarctic Research Expedition. The chlorophyll α concentration was low (less than 0.2mg/m^3) in the Subtropical Water, which became a little higher in the Subantarctic Water and the maximum values of 0.50 and 0.24mg/m^3 were observed on the north side of the Antarctic Convergence (AC). The value was generally low in the open water south of the AC, but high values of 0.84 (58°S) and 0.58 (62°S) mg/m^3 were measured farther south of the AC in the southward and northward legs respectively. In or near the pack ice water, the chlorophyll α concentration formed a peak in the westward leg in December 1980 where the water temperature and salinity decreased. In a polynya surrounded by the fast ice, high values of 0.66 and 0.80mg/m^3 were recorded, whereas in the pack ice water, the value was low in the northward leg different from the results in the westward leg. These results suggest a relation between the chlorophyll α concentration and the presence of sea ice. departmental bulletin paper